Analysing the Improper Pronunciation of Diphthongs by Iraqi EFL learners - Mukhalad Malik Almutalabi (Masyarakat Linguistik Indonesia Universitas Andalas, 2018)
The current study aims at analysing the improper pronunciation of Iraqi EFL learners concerning the pronunciation of diphthongs in words of various syllables. It describes and identifies thoroughly the mispronunciations of such important sounds in English language. The study attempts at analysing such mispronunciations by clarifying and assigning the phonetic deviations of Iraqi EFL learners when they pronounce diphthongs. So the main objective of the study is to analyse the errors committed by Iraqi learners in the pronunciation of diphthongs grouping each error into its specific category. To verify the objective of the paper, 25 Iraqi EFL learners from the department of English at Cihan University/ Slemani are chosen to be the main participants of the study. The test which was conducted in the laboratory of the Department of English contained 10 words comprising various diphthongs. The results clearly revealed that mispronouncing English diphthongs by Iraqi EFL were mostly observed by replacing the required diphthong with another improper one and they also tended to use simple vowels instead of the correct required diphthongs.